Dietary fat and gut microbiota interactions determine diet-induced obesity in mice - Kübeck, Raphaela; Bonet-Ripoll, Catalina; Hoffmann, Christina; Walker, Alesia; Müller, Veronika Maria; Schüppel, Valentina Luise; Lagkouvardos, Ilias; Scholz, Birgit; Engel, Karl-Heinz; Daniel, Hannelore; Schmitt-Kopplin, Philippe; Haller, Dirk; et al. (Molecular metabolism (Germany), 2016)
Gut microbiota may promote positive energy balance; however, germfree mice can be either resistant or susceptible to diet-induced obesity (DIO) depending on the type of dietary intervention. We here sought to identify the dietary constituents that determine the susceptibility to body fat accretion in germfree (GF) mice. GF and specific pathogen free (SPF) male C57BL/6N mice were fed high-fat diets either based on lard or palm oil for 4 wks. Mice were metabolically characterized at the end of the feeding trial. FT-ICR-MS and UPLC-TOF-MS were used for cecal as well as hepatic metabolite profiling and cecal bile acids quantification, respectively. Hepatic gene expression was examined by qRT-PCR and cecal gut microbiota of SPF mice was analyzed by high-throughput 16S rRNA gene sequencing. GF mice, but not SPF mice, were completely DIO resistant when fed a cholesterol-rich lard-based high-fat diet, whereas on a cholesterol-free palm oil-based high-fat diet, DIO was independent of gut microbiota. In GF lard-fed mice, DIO resistance was conveyed by increased energy expenditure, preferential carbohydrate oxidation, and increased fecal fat and energy excretion. Cecal metabolite profiling revealed a shift in bile acid and steroid metabolites in these lean mice, with a significant rise in 17β-estradiol, which is known to stimulate energy expenditure and interfere with bile acid metabolism. Decreased cecal bile acid levels were associated with decreased hepatic expression of genes involved in bile acid synthesis. These metabolic adaptations were largely attenuated in GF mice fed the palm-oil based high-fat diet. We propose that an interaction of gut microbiota and cholesterol metabolism is essential for fat accretion in normal SPF mice fed cholesterol-rich lard as the main dietary fat source. This is supported by a positive correlation between bile acid levels and specific bacteria of the order Clostridiales (phylum Firmicutes) as a characteristic feature of normal SPF mice fed lard. In conclusion, our study identified dietary cholesterol as a candidate ingredient affecting the crosstalk between gut microbiota and host metabolism. •Cholesterol-based but not plant sterol-based high-fat diet protects germfree (GF) mice from diet-induced obesity (DIO).•DIO resistant GF mice show preferential carbohydrate oxidation, higher energy expenditure and energy and fat excretion.•DIO resistance in GF mice is accompanied by increased steroid hormone levels but decreased bile acid levels in the cecum.•Substrate oxidation and fat excretion in DIO resistant GF mice is linked to decreased hepatic Cyp7a1 and Nr1h4 expression.